Pengembangan Lembar Kerja Siswa (LKS) Berbasis Inkuiri Terbimbing pada Materi Pokok Laju Reaksi untuk Siswa Kelas XI IPA SMA - Lukmanul Hakim.S; Sugiarti Sugiarti; Jusniar Jusniar (Jurusan Kimia FMIPA UNM, 2020)
This study aims to describe and compare critical thinking skills of students based This research is research and development which aims to arrange and develop student worksheet for Senior High School grade XI based on guided inquiry based on KTSP that can be used as reference or alternative of media for teacher in chemistry instruction in the class and in the laboratory and it also can be used by students as addition of learning source and to know the properness of student worksheet based on guided inquiry. This research subject is students of class XI IPA2 SMA Negeri 2 Polewali in the amount of 32 people with details of 6 men and 26 women. The development of this student worksheet refers to developmental model of 4-D by Thiagarajan, et al that included define phase, design phase, and develop phase. Fourth phase is disseminate was not done. This student worksheet has already validated by validator and through limited try out, as well as revised many times by developer so that obtain valid, effective and practical result. This research showed that: (1) average score of students learning achievement is 81 from ideal score 100 with class completeness 81.25% or amount of 26 complete score students; (2) students activities in psychomotor and affective aspect showed positive tendency with each percentage for psychomotor is in high category is in the amount of 81.25% and in very high category is in the amount of 18.75% while for affective aspect has total average values percentage of whole affective scoring indicators is in the amount of 91% which is categorized very high; (3) commonly students gave positive responses toward used student worksheet with percentage that expressed very good, good, less good is in the amount of 37.50%, 59.38%, and 3.12% in a series, as are teachers responses which gave very positive responses totality with percentage 100% expressed very good with amount of teachers gave responses is 3 chemistry teachers.